2021
DOI: 10.1071/sh20175
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to pre-exposure prophylaxis among African migrants in high income countries: a systematic review

Abstract: Background: The aim of this review is to explore acceptability, barriers, and facilitators to PrEP use among African migrants in high-income countries. Methods: A systematic review was conducted to explore reasons that contribute to low PrEP uptake in this population. Three online databases, abstracts from key conferences and reference lists of relevant studies articles published between the 2 July 2018 and 3 March 2019 were searched. Narrative synthesis was performed on quantitative data and thematic synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The common reports of stigma hindering uptake of PrEP among our study participants were similar to the findings from other studies [11,31]. For example, research on uptake of PrEP has reported that stigma associated with being labelled as HIV-infected and being suspected of infidelity or promiscuity, was a barrier to uptake of PrEP [11,32,33].…”
Section: Plos Onesupporting
confidence: 86%
“…The common reports of stigma hindering uptake of PrEP among our study participants were similar to the findings from other studies [11,31]. For example, research on uptake of PrEP has reported that stigma associated with being labelled as HIV-infected and being suspected of infidelity or promiscuity, was a barrier to uptake of PrEP [11,32,33].…”
Section: Plos Onesupporting
confidence: 86%
“…In Uganda, PrEP was initially offered in a few accredited antiretroviral therapy (ART) sites with the capacity to provide a complete package. It has not yet been rolled out to all health facilities in the country [ 12 , 13 ]. The Ugandan ministry of health (MoH) started the national PrEP rollout for HIV prevention in 2017 and this scale-up began with serodiscordant couples (SDC) and has since expanded to other MARPs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prescription of these prevention tools, which are reimbursed by social security, is recommended by the French health authorities in populations most vulnerable to HIV acquisition, mainly men who have sex with men (MSM) and people born in sub-Saharan Africa [ 10 ]. However, to date, limited research has been conducted to assess the state of knowledge of these treatments among immigrants from sub-Saharan Africa, both in France and in other Western countries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%